2006
DOI: 10.1063/1.2404613
|View full text |Cite
|
Sign up to set email alerts
|

Complete set of elastic, dielectric, and piezoelectric coefficents of 0.93Pb(Zn1∕3Nb2∕3)O3–0.07PbTiO3 single crystal poled along [011]

Abstract: The authors report a complete set of elastic, dielectric, and piezoelectric coefficients of rhomboheral phase 0.93Pb͑Zn 1/3 Nb 2/3 ͒O 3-0.07PbTiO 3 single crystal poled along ͓011͔ measured at room temperature. It was found that the electromechanical coupling coefficients k 32 and k 33 of this domain engineered single crystal can reach 0.86 and 0.87, respectively, and the piezoelectric coefficients d 32 and d 15 are −1460 and 1823 pC/ N, respectively. This complete set of data can meet the urgent need of devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 24 publications
0
56
0
1
Order By: Relevance
“…These modes are ͑001͒ / ͗100͘, ͑001͒ / ͗110͘, ͑110͒ / ͗001͘, and ͑110͒ / ͗−110͘, where the first number indicates the electrode face and the second number is the acoustic wave propagation direction. 5 It has been demonstrated that the highest transverse piezoelectric coefficients are obtained from crystals poled along ͗110͘ and vibrated along the ͗001͘ direction, [5][6][7][8][9][10] with small signal d 32 coefficients on the order of ϳ−1500 pC/ N and electromechanical coupling factor k 32 ϳ 0.90 in PZNT and PMNT crystals.…”
Section: Introductionmentioning
confidence: 99%
“…These modes are ͑001͒ / ͗100͘, ͑001͒ / ͗110͘, ͑110͒ / ͗001͘, and ͑110͒ / ͗−110͘, where the first number indicates the electrode face and the second number is the acoustic wave propagation direction. 5 It has been demonstrated that the highest transverse piezoelectric coefficients are obtained from crystals poled along ͗110͘ and vibrated along the ͗001͘ direction, [5][6][7][8][9][10] with small signal d 32 coefficients on the order of ϳ−1500 pC/ N and electromechanical coupling factor k 32 ϳ 0.90 in PZNT and PMNT crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, [011] c PMN-xPT relaxor ferroelectric single crystals, with compositions near the MPB, come into view due to their high transverse piezoelectric properties (d 31 > 2100 pC/N) [10][11][12][13][14]. Meanwhile, [011] c orthorhombic relaxor-PT crystal was reported with a high shear piezoelectric response of d 24 in single domain state, making it a promising candidate for novel sensor or transducer design [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric crystals such as Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) and Pb(Zn 1/3 Nb 2/3 )O 3 -PbTiO 3 (PZN-PT) with morphotropic phase boundary (MPB) have been reported to exhibit excellent piezoelectric, electromechanical, and dielectric properties, which lead them to be promising candidates for high performance actuators and transducers [1][2][3][4][5][6]. However, their relatively low temperature of the maximum dielectric constant (T max ) and even lower depolarization temperature (T MPB ) greatly limit the applications in many fields, where the broad temperature range is desired.…”
Section: Introductionmentioning
confidence: 99%